Aggressive behavior among women with intellectual disabilities receiving institutional long-term care - Bojana Mastilo; Bojana Vuković; Stevan Šeatović; Sladjana Ćalasan (Биомедицинска истраживања, 2019)
Introduction: Aggressive behavior is defined as the behavior of such intensity, frequency and duration that it seriously threatens the physical safety of a person/persons or the one which seriously limits their social functioning. The aim of the paper is to determine the intensity and forms of aggression in institutionalized women with intellectual disabilities, in relation to the severity of their intellectual disability, age, as well as the length of stay in the institutional settings. Methods: The sample comprised 115 female examinees receiving institutional long-term care in PI "The Center for People with Disabilities" in Visegrad. The Adult Scale of Hostility and Agression, Reactive/Proactve A-SHARP (Matlock & Aman, 2011) was used for the assessment of aggressive behavior. Results: The results revealed that women with mild intellectual disabilities showed high aggression on all subscales, with the highest scores on the Hostility subscale (26.37 ± 7.37). In the group of examinees aged ?51 years, there was a statistically significant difference on the Verbal aggression subscale compared to the group of women aged ?30 years (13.89 ± 9.23 vs. 6.12 ± 9.39; p = 0.025). In the group of examinees who had stayed in the institutional settings for ?10 years, a display of hostile aggression was more extreme compared to the group of patients with shorter length of stay in the institutional settings (22.49 ±11.22 vs. 17.58 ± 13.14; p = 0.033). Conclusion: Women with mild intellectual disabilities showed the highest level of aggressive behavior on all subscales, whereby the highest scores were recorded on the Hostility subscale. Women aged ?51 years showed the highest level of verbal aggression, while the examinees who had stayed in the institutional settings for ?10 years displayed the highest level of hostile aggression towards others.
Keywords: aggressive behavior; intellectual disability; institution